Hollow Hemispherical Carbon Microspheres with Mo2C Nanoparticles Synthesized by Precursor Design: Effective Noble Metal‐Free Catalysts for Dehydrogenation. Issue 1 (11th November 2019) - Zhao, Ruihua; Wang, Hui; Gao, Na; Liu, Rui; Guo, Tianyu; Wu, Jinting; Zhang, Tao; Li, Jinping; Du, Jianping; Asefa, Tewodros
Abstract: Noble metal‐based catalysts are currently widely used for the dehydrogenation of hydrocarbons or the production of H2 from hydrocarbons for various applications. However, these catalysts are expensive and hard to scale up. In this work, a facile template‐assisted synthesis of hollow carbon microspheres possessing ultrasmall molybdenum carbide (Mo2 C) nanoparticles (NPs) that can efficiently catalyze the dehydrogenation of hydrocarbons is reported. The hollow structures and catalytic activity of the materials can be tuned, or optimized, by controlling the relative amount of Mo species or template used in their precursors. The bowl‐like hemispherical carbons with ≈20 nm thin shells and <5 nm in diameter Mo2 C NPs show superior catalytic activity for dehydrogenation of cyclohexane, with a turnover frequency value of 1 × 10 −4 s −1 at 305 °C. The catalytic activity of these microspheres for the reaction is 15 times higher than that of the corresponding incomplete hollow spherical carbon microparticles possessing similar sized Mo2 C NPs and also better than that of activated carbon‐supported Pt (Pt/AC). Interestingly also, adding a mere 0.1% Pt into the materials leads to several‐fold increase in their catalytic activity and much higher activity than that of Pt/AC. Abstract : Hollow hemispherical carbon microparticles possessing Mo2 C nanoparticles are synthesized from easily available precursors using soft and hard templates. The microparticles show excellent and stable catalytic activities for the dehydrogenation of cyclohexane. The materials have the potential to serve as alternative catalysts to noble metals, which are currently widely used for this reaction.